O discurso de intolerância religiosa no filme O pagador de promessas sob a perspectiva da análise do discurso ecológica - Luiz, Michelly Jacinto Lima (2018)
The object of study of this dissertation is the discourse of religious intolerance presented in the movie The Payer of Promises (1962). The film under study has already been the object of investigation of research in the academy, in the areas of Literature and Arts. However, after investigation we find that this film work has never been analyzed from the assumptions of the Ecological Discourse Analysis. The film "The Payer of Promises" portrays the story of the ideological clash between Father Olavo (represented by Dionísio Azevedo) and the protagonist Zé do Burro (represented by Leonardo Villar). In summary, the work tells the story of Zé do Burro, who makes a promise to Santa Barbara to reach the cure of his pet donkey and, when he obtains the desired grace, begins his pilgrimage. In an attempt to pay his promise, he tells the priest that he had made a promise to the saint in a candomblé backyard, where he promised that if his pet donkey were cured he would carry a cross as heavy as that of Christ to the Church Of Santa Bárbara, besides dividing its lands equally with the other farmers of the region. However, the priest does not allow Zé do Burro to enter the church, because of his promise to have been held in a candomblé backyard, which will generate the whole clash in the film work. The strength and timeliness of this plot is what motivated the theme of this dissertation: the discourse of religious intolerance in the movie The Payer of Promises from the perspective of the Ecological Discourse Analysis. Thus, the overall objective of this research is to demonstrate how religious intolerance leads to suffering in its natural, mental and social contexts and how the film is representative of it. As a theoretical contribution, we use the Ecological Discourse Analysis, which is inserted in the context of the ecosystemic linguistics, which is part of the Ecolinguistics practiced in Brazil, the Anthropology of the Imaginary as well as the Fundamentals of Film Analysis. The methodological procedures used here include the film analysis, the criticalmyth and the methodology applied by ADE. In this way, it was possible to observe from the perspective of the Ecological Discourse Analysis that all the suffering that the characters are exposed in the course of the film narrative are motivated by the cultural disjunctions and the non acceptance of the diversity, due to the religious intolerance.